2009
DOI: 10.1038/cr.2009.79
|View full text |Cite
|
Sign up to set email alerts
|

Cross-regulation of the Nanog and Cdx2 promoters

Abstract: The first cell fate choice in the mammalian embryo, the segregation of the inner cell mass (ICM) and trophectoderm (TE), is regulated by the mutually antagonistic effects of the transcription factors, Oct4 and Cdx2, while the pluripotency factor, Nanog, is essential to specify the epiblast. We have analyzed the promoters of Nanog and Cdx2, and have found that these two transcription factors are likewise regulated reciprocally. Using an embryonic stem cell line with conditional TE differentiation, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
106
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 23 publications
9
106
3
Order By: Relevance
“…Cdx2 expression is directly repressed by Oct4 or Nanog, and repression of Nanog or Oct4 expression was shown to enhance Cdx2 expression (14,46). In our study, decreased SMAD2 expression in hESCs resulted in repression of NANOG and OCT4 expression and enhanced CDX2 expression through increased BMP signaling.…”
Section: Activation Of Nanog Expression and Suppression Of Bmp Signalmentioning
confidence: 57%
See 1 more Smart Citation
“…Cdx2 expression is directly repressed by Oct4 or Nanog, and repression of Nanog or Oct4 expression was shown to enhance Cdx2 expression (14,46). In our study, decreased SMAD2 expression in hESCs resulted in repression of NANOG and OCT4 expression and enhanced CDX2 expression through increased BMP signaling.…”
Section: Activation Of Nanog Expression and Suppression Of Bmp Signalmentioning
confidence: 57%
“…Furthermore, Cdx2 binds Oct4 and Nanog gene promoter sequences, and Oct4 and Nanog can bind the Cdx2 promotor, conferring reciprocal repression (14,46). Therefore, decreased OCT4 expression in hESCs with decreased SMAD2 expression (Fig.…”
Section: Suppressing Cdx2 Expression Rescues Decreased Oct4 But Not mentioning
confidence: 99%
“…CDX2 expression was found to be directly related to IFNτ expression along with the embryo development until the hatching stage in both BT-and AF-derived blastocysts suggesting that CDX2 is a potent regulator of IFNτ expression [22,33,34] while it showed no change in IVF-produced blastocysts.…”
Section: Discussionmentioning
confidence: 98%
“…The maintenance of pluripotency depends on OCT4 and NANOG functions during preimplantation development (Chen et al, 2009;Mitsui et al, 2003;Nichols et al, 1998;Shao et al, 2008). Pou5f1 and Nanog, both of which are ICM markers, negatively interact with Cdx2, a TE marker, and these three genes are key regulators in cell fate specification (Chen et al, 2009;Niwa et al, 2005;Ralston et al, 2010;Strumpf et al, 2005). Pou5f1 or Nanog knockout mouse embryos can develop into morphologically normal blastocysts; however, developmental arrest occurs during the postimplantation period due to a loss of pluripotency (Mitsui et al, 2003;Nichols et al, 1998;Ralston et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we showed that the rescue of HMGPI had no effect on Klf5 expression in Chd1-knockdown-Hmgpi-rescue embryos, suggesting that there is no direct interaction between Hmgpi and Klf5 during preimplantation development. The maintenance of pluripotency depends on OCT4 and NANOG functions during preimplantation development (Chen et al, 2009;Mitsui et al, 2003;Nichols et al, 1998;Shao et al, 2008). Pou5f1 and Nanog, both of which are ICM markers, negatively interact with Cdx2, a TE marker, and these three genes are key regulators in cell fate specification (Chen et al, 2009;Niwa et al, 2005;Ralston et al, 2010;Strumpf et al, 2005).…”
Section: Discussionmentioning
confidence: 99%